2017
DOI: 10.31234/osf.io/9jr45
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The influence of age on the take-over of vehicle control in highly automated driving

Abstract: The growing proportion of older drivers in the population plays an increasingly relevant role in road traffic that is currently awaiting the introduction of automated vehicles. In this study, it was investigated how older drivers (⩾60 years) compared to younger drivers (⩽28 years) perform in a critical traffic event when driving highly automated. Conditions of the take-over situation were manipulated by adding a verbal non-driving task (20 questions task) and by variation of traffic density. Two age groups con… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 18 publications
4
33
1
Order By: Relevance
“…However, no significant differences were observed between the three groups as far as the time to collision is concerned. Furthermore, according to the age group, no significant differences were observed regarding the reaction time nor the maximum lateral position; this result is in agreement with Korber et al [23] who found that older drivers handle critical traffic events and adapt to the experience of take-over situations as well as younger drivers. Finally, considering the TOR caused by loss of road marking, the stability of the trajectory in the 30 seconds after the TOR was evaluated and no significant differences between the groups were observed comparing the maximum lateral distance from the center of the lane.…”
Section: Objective and Performance Measuressupporting
confidence: 90%
See 2 more Smart Citations
“…However, no significant differences were observed between the three groups as far as the time to collision is concerned. Furthermore, according to the age group, no significant differences were observed regarding the reaction time nor the maximum lateral position; this result is in agreement with Korber et al [23] who found that older drivers handle critical traffic events and adapt to the experience of take-over situations as well as younger drivers. Finally, considering the TOR caused by loss of road marking, the stability of the trajectory in the 30 seconds after the TOR was evaluated and no significant differences between the groups were observed comparing the maximum lateral distance from the center of the lane.…”
Section: Objective and Performance Measuressupporting
confidence: 90%
“…To study driver's distraction during automated driving, researchers generally use standardized and naturalistic tasks. Standardized tasks (such as the cognitive n-back task [21], the SuRT task 140 [21,22], the Twenty Questions Task (TQT) [23]) provide experimental control, but they do not usually correspond to what the driver will do in the vehicle. Naturalistic tasks, instead, provide ecological validity, but they could introduce experimental bias.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, conditionally automated vehicles need to allow for a "sufficiently comfortable transition time" [12] of "several seconds" after presenting a TOR [5]. In an attempt to gain an understanding of how long drivers need to resume control from an automated vehicle, Eriksson and Stanton [13] reviewed the literature on control transitions and found that drivers take a median of 2.5 s, and in some cases up to 15 s to resume control in urgent scenarios (e.g., [14]). Their review also showed that when drivers are requested to resume control without time pressure, they take between 2.1 and 3.5 s (median) longer than when under time pressure, depending on task engagement [13].…”
Section: A Importance Of Hmis In Take-over Scenariosmentioning
confidence: 99%
“…Arguably, with age come changes in the way the driving task is performed, and studies looking into driver skill are inevitably confounded by this variable, a factor recognized across driving research [37]. In controlled experiments exploring takeover performance and age, Körber et al [38] found little differences in behavioral performance when drivers were asked to take control with and without a secondary task. Morgan et al [8] argued that most handover studies focused on mainly middle-aged and high-mileage drivers.…”
Section: Driver Skill In C/havsmentioning
confidence: 99%